Pembangunan pendidikan dan kelestarian sumber manusia di Felda - Noraziah Ali,; Noorzah Zakaria,; Mohd Azlan Abdullah, (2010)
Educational factors is the most important element in the development of human resources. Educational development in FELDA aims to produce human resources with potential among the second generation who are knowledgeable, responsible and competitive. These study was conducted to examine the development of education and its implications in FELDA and in the Felda Bersia, Grik, Perak in particular. Field data collection was conducted between June and August 2007. There were various programmes implemented to improve settlers children's education performance. Programmes effectiveness can be measured based on the results of UPSR, PMR and SPM. In general, the academic performance among students in FELDA has improved, including a handful of successes. However, FELDA did not provide further educational and employment opportunities in the land schemes, causing most of the second generation migrating to the cities, either to further their study or to work. The implication of the development of education in FELDA has produced many successful individuals, but not in the schemes. Consequently, the development of FELDA itself depends on old settlers and human resources of the second generation who are less excellent.